Efficacy of five different traditional Chinese medicine injections in acute upper respiratory tract infection in children: a network meta-analysis and systematic review - Guo, Xinyi; Liu, Changxing; Zhao, Qiong; Huang, Sajiyue (Frontiers in Pediatrics, 2024)
Background Acute upper respiratory tract infection (AURI) includes infections caused by a variety of pathogens and is one of the most common diseases in children. Traditional Chinese medicine (TCM) injections are widely used for treating AURI in clinical practice, but their efficacy is unclear because of the lack of clear evidence. In this study, a network meta-analysis (NMA) was used to evaluate the efficacy and safety of TCM injections in the treatment of AURI and to provide a reference for clinical treatment. Methods Eight databases were searched, namely, PubMed, Embase, the Cochrane Library, Web of Science, SinoMed, China National Knowledge Infrastructure (CNKI), the Wanfang database, and the Chinese Scientific Journal database (VIP). The search time period was from 1 January 2013 to 1 November 2023. Randomized controlled trials of herbal injections for treating AURI were searched. The Cochrane Risk of Bias 2.0 tool was used to assess the quality of these studies. Review Manager 5.4 and Stata 15.0 were used for the NMA. Results A total of 81 papers involving 11,736 patients were included. These involved five different TCM injections, namely, Xiyanping injection (XYPI), Qingkailing injection (QKLI), Reduning injection (RDNI), Yanhuning injection (YHNI), and Tanreqing injection (TRQI). QKLI was most effective in alleviating symptoms of fever and improving overall clinical effectiveness. TRQI was most effective in relieving cough symptoms. YHNI was most effective in alleviating sore throat, runny nose, and nasal congestion. The overall incidence of adverse effects of these herbal injections in the treatment of AURI was lower, and their safety profiles were better. Conclusions The herbal injections combined with ribavirin improved clinical outcomes, and were superior to ribavirin injection alone in alleviating clinical symptoms such as fever, cough, sore throat, runny nose, and nasal congestion, and have favorable safety profiles. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023484099, CRD42023484099.